Effects of Propofol on Hemodynamic Profile in Adults Receiving Targeted Temperature Management. (June 2022) - Hawkins, W. Anthony; Kim, Jennifer Y.; Smith, Susan E.; Sikora Newsome, Andrea; Hall, Ronald G.
Background: Propofol is a key component for the management of sedation and shivering during targeted temperature management (TTM) following cardiac arrest. The cardiac depressant effects of propofol have not been described during TTM and may be especially relevant given the stress to the myocardium following cardiac arrest. The purpose of this study is to describe hemodynamic changes associated with propofol administration during TTM.Methods: This single center, retrospective cohort study evaluated adult patients who received a propofol infusion for at least 30 minutes during TTM. The primary outcome was the change in cardiovascular Sequential Organ Failure Assessment (cvSOFA) score 30 minutes after propofol initiation. Secondary outcomes included change in systolic blood pressure (SBP), mean arterial pressure (MAP), heart rate (HR), and vasopressor requirements (VR) expressed as norepinephrine equivalents at 30, 60, 120, 180, and 240 minutes after propofol initiation. A multivariate regression was performed to assess the influence of propofol and body temperature on MAP, while controlling for vasopressor dose and cardiac arrest hospital prognosis (CAHP) score.Results: The cohort included 40 patients with a median CAHP score of 197. The goal temperature of 33°C was achieved for all patients. The median cvSOFA score was 1 at baseline and 0.5 at 30 minutes, with a non-significant change after propofol initiation ( P = .96). SBP and MAP reductions were the greatest at 60 minutes (17 and 8 mmHg; P < .05 for both). The median change in HR at 120 minutes was −9 beats/minute from baseline. This reduction was sustained through 240 minutes ( P < .05). No change in VR were seen at any time point. In multivariate regression, body temperature was the only characteristic independently associated with changes in MAP (coefficient 4.95, 95% CI 1.6-8.3).Conclusion: Administration of propofol during TTM did not affect cvSOFA score. The reductions in SBP, MAP, and HR did not have a corresponding change in vasopressor requirements and are likely not clinically meaningful. Propofol appears to be a safe choice for sedation in patients receiving targeted temperature management after cardiac arrest.